Model for the management of water resources in the Las Bambas basin - Romero Baylón, Alfonso (2005)
915/5000       The purpose of this work is to show a management model of the water resources of the different basins that make up the Bambas Basin in Apurímac, with the purpose of contributing to the primary extractive industry in a sustainable way. There are various computer applications for basin modeling and, due to its multidisciplinary nature and specific specialty of the subject, for an integral modeling several of them must be used, among these we can mention the HidroGeolAnalyst, ModFlow, GeoChemestry, among others, with which surface and / or underground water modeling can be done in its lagoon and aquifer aspects, respectively. This work proposes the application of the use of water resources in the area, thus suggesting that prospecting and exploration works should consider these aspects within their respective campaigns.